Colonization With Fluoroquinolone-Resistant Enterobacterales Decreases the Effectiveness of Fluoroquinolone Prophylaxis in Hematopoietic Cell Transplant Recipients. (6th May 2021) - Satlin, Michael J; Chen, Liang; Douglass, Claire; Hovan, Michael; Davidson, Emily; Soave, Rosemary; La Spina, Marisa; Gomez-Arteaga, Alexandra; van Besien, Koen; Mayer, Sebastian; Phillips, Adrienne; Hsu, Jing-Mei; et al.
Abstract: Background: Levofloxacin prophylaxis is recommended to prevent gram-negative bloodstream infections (BSIs) in patients with prolonged chemotherapy-induced neutropenia. However, increasing fluoroquinolone resistance may decrease the effectiveness of this approach. Methods: We assessed the prevalence of colonization with fluoroquinolone-resistant Enterobacterales (FQRE) among patients admitted for hematopoietic cell transplantation (HCT) from November 2016 to August 2019 and compared the risk of gram-negative BSI between FQRE-colonized and noncolonized patients. All patients received levofloxacin prophylaxis during neutropenia. Stool samples were collected upon admission for HCT and weekly thereafter until recovery from neutropenia, and underwent selective culture for FQRE. All isolates were identified and underwent antimicrobial susceptibility testing by broth microdilution. FQRE isolates also underwent whole-genome sequencing. Results: Fifty-four of 234 (23%) patients were colonized with FQRE prior to HCT, including 30 of 119 (25%) allogeneic and 24 of 115 (21%) autologous HCT recipients. Recent antibacterial use was associated with FQRE colonization ( P  = .048). Ninety-one percent of colonizing FQRE isolates were Escherichia coli and 29% produced extended-spectrum β-lactamases. Seventeen (31%) FQRE-colonized patients developed gram-negative BSI despite levofloxacin prophylaxis, compared to only 2 of 180 (1.1%) patients who were not colonized with FQRE on admission ( P  < .001). Of the 17 gram-negative BSIs in FQRE-colonized patients, 15 (88%) were caused by FQRE isolates that were genetically identical to the colonizing strain. Conclusions: Nearly one-third of HCT recipients with pretransplant FQRE colonization developed gram-negative BSI while receiving levofloxacin prophylaxis, and infections were typically caused by their colonizing strains. In contrast, levofloxacin prophylaxis was highly effective in patients not initially colonized with FQRE. Abstract : Twenty-three percent of 234 hematopoietic cell transplant recipients were colonized with fluoroquinolone-resistant Enterobacterales (FQRE) upon admission for their transplantation. Thirty-one percent of FQRE-colonized patients developed gram-negative bloodstream infection despite levofloxacin prophylaxis, compared to 1.1% of noncolonized patients.